2018
DOI: 10.3324/haematol.2018.203166
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the effect of silent, intronic and missense mutations on VWF splicing: contribution of next generation sequencing in the study of mRNA

Abstract: Large studies in von Willebrand disease patients, including Spanish and Portuguese registries, led to the identification of >250 different mutations. It is a challenge to determine the pathogenic effect of potential splice site mutations on VWF mRNA. This study aimed to elucidate the true effects of 18 mutations on VWF mRNA processing, investigate the contribution of next-generation sequencing to in vivo mRNA study in von Willebrand disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…After applying in silico predictive tools to 41 variants previously classified as missense variants, the authors demonstrated that over 45% of them were shown to affect splicing and claimed that such variants have been frequently underscored if not analysed in depth. These observations were further supported by studies using next-generation sequencing technology [32] and highthroughput splicing reporter assays [35] to unravel the effect on splicing of single nucleotide variants, including missense, in the von Willebrand factor gene and POU1F1, respectively. Altogether, there is a need for improvement of in silico tools to predict cryptic splicing, and for the development of guidelines for formal analysis of splicing defects induced by SNVs, particularly synonymous and missense variants.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…After applying in silico predictive tools to 41 variants previously classified as missense variants, the authors demonstrated that over 45% of them were shown to affect splicing and claimed that such variants have been frequently underscored if not analysed in depth. These observations were further supported by studies using next-generation sequencing technology [32] and highthroughput splicing reporter assays [35] to unravel the effect on splicing of single nucleotide variants, including missense, in the von Willebrand factor gene and POU1F1, respectively. Altogether, there is a need for improvement of in silico tools to predict cryptic splicing, and for the development of guidelines for formal analysis of splicing defects induced by SNVs, particularly synonymous and missense variants.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding the impact that complete or incomplete downregulation of the mutant allele may have for disease phenotype and severity, very little is known. However, it has been documented that certain genetic modifiers, and interindividual variability in NMD efficiency between patients carrying identical mutations, may lead to differences in the disease severity and clinical phenotype [32].…”
Section: Discussionmentioning
confidence: 99%
“…Von Willebrand disease is one of the most common inherited bleeding disorders, caused by any one of hundreds of mutations in the VWF gene [23, 24]. The mutation studied here, although present at low frequency among the populations surveyed (dbSNP: rs900907976 ; minor allele frequency=0.000026 (7/264690, TOPMED), has an unusual impact on pre-mRNA splicing by acting at a distance to promote retention of the downstream intron [16].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, VWF mutational analysis can be valuable for diagnosing and investigating the molecular etiology of VWD. 4 The prediction softwares used (SpliceSiteFinder-like, MaxEntScan, GeneSplicer, NSPLICE, ESEFinder, RESCUE-ESE, and EX-SKIP) regarding c.1530G > A (p.(Val510 = )) interpreted the appearance of a donor site at 6 base pairs at the end of exon 13 which could potentially alter splicing. This synonymous mutation could therefore have an effect on VWF messenger ribonucleic acid processing, causing a shift in the reading frame and the appearance of a termination codon deletion of two codons.…”
Section: Figmentioning
confidence: 99%